EFFECTIVENESS OF PROPOSED EDUCATIONAL UNITS USING ELECTRONIC THINKING MAPS IN ACHIEVEMENT AND DEVELOPING ANALYTICAL THINKING AMONG STUDENTS OF THE COLLEGE OF EDUCATION - Al-Mayyahi, Ethar Abdul mohsin Qasim (Journal of Higher Education and Academic Advancement, 2024)
This research aims to evaluate the educational unit's performance using electronic thinking maps in achievement and developing analytical thinking among two groups 30 students each, at grade 3 of the College of Education as compared to normal conventional teaching methods. The grade averages were compared between the two experimental groups (P≤0.05) in 2022-2023. The two groups were assessed for variables (chronological age - intelligence - previous knowledge, pre-analytical thinking test), and research requirements were prepared. Necessary, represented by the scientific material, its topics, behavioural objectives, and teaching plans for each group. The research tools included the achievement and the analytical thinking test. data was processed statistically using the statistical package for the social sciences (SPSS). The result showed that the experimental group studied according to proposed educational units using electronic thinking maps showed significantly higher evaluation in terms of achievement and developing analytical thinking than the students of the control group that studied according to the usual method. In light of the research results, using electronic thinking maps for curricula and teaching methods is highly recommended to be taught in colleges of education in Iraq. Thus, teachers would be more satisfied as using necessity of diversity in the use of modern teaching strategies and educational techniques. That will emphasize the positive role of the student in the learning process. This type of thinking maps can be successfully used in teaching curricula and teaching methods that could be suggested to other colleges and institutes of education.